2016
DOI: 10.1556/2006.5.2016.028
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity in Multiplayer Online Battle Arena Gamers: Preliminary Results on Experimental and Self-Report Measures

Abstract: Background and aimsMultiplayer Online Battle Arena (MOBA) games have become the most popular type of video games played worldwide, superseding the playing of Massively Multiplayer Online Role-Playing Games and First-Person Shooter games. However, empirical studies focusing on the use and abuse of MOBA games are still very limited, particularly regarding impulsivity, which is an indicator of addictive states but has not yet been explored in MOBA games. In this context, the objective of the present study is to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 22 publications
7
80
1
4
Order By: Relevance
“…Among these, problems of self‐regulation and decision‐making, dysregulation of mood, and reward systems are based on neurobiological deficits that may also explain sex differences . Among the external factors, familial deficits, including intrafamilial violence and poor parental care, and deficient social skills may increase the risk of developing IGD, especially of becoming addicted to MMORPGs or action real‐time strategy (shooter) games such as Multiplayer Online Battle Arena . Finally, several game‐related personally and socially reinforcing factors, as well as steadily improving technical performance, will promote IGD …”
Section: Discussionmentioning
confidence: 99%
“…Among these, problems of self‐regulation and decision‐making, dysregulation of mood, and reward systems are based on neurobiological deficits that may also explain sex differences . Among the external factors, familial deficits, including intrafamilial violence and poor parental care, and deficient social skills may increase the risk of developing IGD, especially of becoming addicted to MMORPGs or action real‐time strategy (shooter) games such as Multiplayer Online Battle Arena . Finally, several game‐related personally and socially reinforcing factors, as well as steadily improving technical performance, will promote IGD …”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that excessive play is more likely to be done by dysfunctional impulsives whereas MMORPGs are more likely preferred by functional impulsives. However, the relationships between self-reported impulsivity and addictive Multiplayer Online Battle Arena (MOBA) game use are not yet clear (Nuyens et al, 2016). Other variables associated with the gamer, like passion and motivation, and the game's own characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results on the learning processes at stake in the decision-making are unclear, firstly due to the lack of studies on this specific process and secondly due to contrasting results with one study finding poorer results among gamers on the IGT [40], and the others not finding any association between the learning process and addiction severity [57]. The two studies using delaydiscounting tasks found that problematic gamers had difficulty in delaying rewards [55,57], which might explain their tendency to play immediately instead of waiting.…”
Section: Discussionmentioning
confidence: 98%
“…For the DDT, the problematic gamers discounted the rewards more steeply than the control participants (i.e., they preferred immediate and smaller rewards opposed to more important delayed ones). Using another task to assess Delay Discounting (i.e., the Single Key Impulsivity Paradigm, SKIP), Nuyens et al [57] replicated these findings. The SKIP is an implicit measure of delay discounting, participants having to wait as long as they can before clicking on a picture.…”
Section: Decision-makingmentioning
confidence: 90%
See 1 more Smart Citation